Relationship between the quality of life and the severity of obstructive sleep apnea syndrome - Lopes,C. (2008)
The effects of sleep disorders on the quality of life (QOL) have been documented in the literature. Excessive sleepiness and altered circadian rhythms may negatively affect ability to learn, employment, and interpersonal relations, and directly degrade QOL. The objective of the present study was to evaluate the impact of obstructive sleep apnea syndrome of varying severity on QOL. The study was conducted on 1892 patients aged 18 years or older referred by a physician to the Sleep Institute, São Paulo, with complaints related to apnea (snoring, excessive daytime sleepiness, hyperarousal, and fatigue). They were submitted to overnight polysomnography for the diagnosis of sleep disorders from August 2005 through April 2006. The patients completed the Epworth Sleepiness Scale and QOL SF-36 sleep questionnaires. They were classified as non-physically active and physically active and not-sleepy and sleepy and the results of polysomnography were analyzed on the basis of the apnea hypopnea index (AHI). The apneic subjects showed a reduction in QOL which was proportional to severity. There was a significant decrease in all domains (physical functioning, role physical problems, bodily pain, general health perceptions, vitality, social functioning, emotional problems, general mental health) for apneics with AHI >30, who generally were sleepy and did not participate in physical activities (P < 0.05). The present study provides evidence that the impact of sleep disorders on QOL in apneics is not limited to excessive daytime sleepiness and that physical activity can contribute to reducing the symptoms. Thus, exercise should be considered as an adjunct interventional strategy in the management of obstructive sleep apnea syndrome.